Development of the compact UV illuminator with single UV lamp - Jong, Dae Kim; Deuk, Ju Lee; Sang, Yoon Kim; Yu, Seop Kim; Hye, Jeong Song; Chan, Young Park (Universiti Kebangsaan Malaysia, 2015)
This paper presents a low-cost method of constructing the compact UV illuminator, which is considered as an important component of a gel documentation system. The procedure involves using a smallest-possible UV lamp and a motor which moves the UV lamp in the UV illuminator instead of conventional 4 UV lamps. A comparative analysis of images produced by using the commercial gel documentation system and our prototype was carried out. These comparisons were done in real DNA gel as well as a reference plate made of quantum dot. The plate was composed of the chambers filled with various densities of the quantum dot instead of the Agarose gel containing the ETBR in order to increase the accuracy of comparison and the convenience of experiments. Despite the use of only 1 UV lamp, the proposed system demonstrated a similar imaging performance compared with the conventional gel documentation system equipped with 4 UV lamps, resulting in the great reduction of the system cost.